Catalytic meerwein-ponndorf-verley reductions over mesoporous silica supports: rational design of hydrophobic mesoporous silica for enhanced stability of aluminum doped mesoporous catalysts - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Samuel, Prinson R.; Srilakshmi, Ch; Singh, A. R. (Journal of Molecular Catalysis A-Chemical, 2009)
A series of aluminum isopropoxide-grafted mesoporous organosilica having ethane (-CH(2)-CH(2)-) and ethene (-CH=CH-) groups in the frame wall positions (ethane-silica, ethene-silica) as well as mesoporous silicas (MCM-41, MCM-48. SBA-15) through siloxide linkages were fabricated. The samples were used as catalysts in the Meerwein-Ponndorf-Verley reduction of ketones and aldehydes of different nature and size using secondary alcohols as the hydrogen transfer agents. Aluminum isopropoxide supported mesoporous silica samples show higher catalytic conversion and among them, the one-dimensionally channel oriented Si-MCM-41 supported aluminum isopropoxide shows better results than the three-dimensional Si-MCM-48 and the large pore Si-SBA-15. Compared to aluminum isopropoxide-grafted mesoporous silica samples, aluminum alkoxide-grafted organosilica samples shows better catalytic activity even in the presence of 10% of water and the better stability is attributed to the presence of integrated hydrophobic organic groups in the frame wall positions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aluminum isopropoxide; Mesoporous silica; Organosilica; reduction

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Magnetically separable catalyst for condensation of renewable aldehydes and 2-methylfuran to saturated cyclic oxygenates - Tarade, Komal; Shinde, Suhas; Rode, Chandrashekhar (Fuel Processing Technology, 2020)
The saturated cyclic ethers produced from biomass derived aldehydes and 2-methylfuran are the potential diesel fuel candidates. The synthesis of saturated cyclic ethers is a two step process which involves acid catalyzed condensation of aldehydes with 2-methylfuran and the subsequent selective furan ring hydrogenation of the condensation products. Here, we designed a novel recyclable magnetic solid acid catalyst such as [Fe3O4@SiO2-Pr-Py-H][2HSO(4)(2-)] and employed for the condensation of 2-methylfuran with formaldehyde as model substrates and reaction parameters were optimized. Under the set reaction conditions, condensation of 2-methylfuran with several other aldehydes were also successfully achieved with very good yields. Further, several supported noble metal catalysts were screened in order to find suitable catalyst system for selective furan ring hydrogenation of condensation products. Among those, 5% Pd/C was found to be very active and selective for furan ring hydrogenation without formation of ring opened products under very low hydrogen pressure at room temperature. Prepared catalysts were thoroughly characterized with sophisticated techniques.
Keywords: fuel additives; Hydrogenation; Hydroxyalkylation-alkylation; Magnetic solid acid; Organosilica